Pengaruh Pembiayaan Mudharabah Dan Musyarakah Terhadap Non Performing Financing (Npf) Bank Pembiayaan Rakyat Syariah Di Indonesia Periode 2016-2018 - Hakiki, Mutiara (JYRS: Journal of Youth Research and Studies, 2021)
This type of research is associative with quantitative methods in the form of secondary data taken from islamic banking statistics for 201- 2018 at the financial services authory. Data cillection techniques with documentation and literature study. The data analysis technique used is descprive statistical analysis, regression analysis consisting of normality test, autocorelation, multicollinearity, heteroscedasticity, and hypothesis testing consisting of the F test, T test, R2 test.The result of this study indicate that simultaneously the mudharabah and musharaka financing variables have a significant effect on this, F count with an f value of 4.182538 and a significance value of 0.025045 while partially mudharabah financing has no positif effect with a T value of 0.5771 > 0,05 and musyarakah financing. Has a positive effect on non performing financing with a T value 0.0109 < 0,05.